Concise Synthesis and Fluorescent Properties of Coumarin-30 and Its Isomer 7-(diethylamino)-4-(1-methyl-1H-benzimidazol-2-yl)Coumarin. (October 2016) - Wang, Xiaolong; Zhou, Jingjing; Yang, Fang; Xue, Ziyan; Xu, Niansheng
Coumarin-30 and its regioisomer 7-(diethylamino)-4-(1-methyl-1H-benzimidazol-2-yl)coumarin were synthesised utilising condensation of the corresponding formylcoumarin with N-methylphenylene-1, 2-diamine as the key step. Furthermore, absorption and fluorescence emission spectra of the two coumarins were recorded.